2003
DOI: 10.1590/s0041-87812003000600004
|View full text |Cite
|
Sign up to set email alerts
|

C-cells in colloid goiter

Abstract: These results demonstrate a significant decrease of C-cell number in the colloid goiter group compared with control group, indicating that the hyperplastic process is restricted to follicular cells, to the detriment of C-cells, which probably cease to receive trophic stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…4 It has also been suggested that thyroid function control factors, such as C cells, can alter iodine levels, leading to goitre. 7 According to some studies, iodine deficiency is associated with a 5-10% prevalence of goitre. 8,9 The peak age for the onset of goitre is 35-50 years, and the ratio of women to men affected by goitre is 3:1.…”
Section: Aetiology and Epidemiologymentioning
confidence: 99%
“…4 It has also been suggested that thyroid function control factors, such as C cells, can alter iodine levels, leading to goitre. 7 According to some studies, iodine deficiency is associated with a 5-10% prevalence of goitre. 8,9 The peak age for the onset of goitre is 35-50 years, and the ratio of women to men affected by goitre is 3:1.…”
Section: Aetiology and Epidemiologymentioning
confidence: 99%
“…Distribuição (Fig. 78): Brasil [Goiás, Distrito Federal, Mato Grosso do Sul, Minas Gerais (Monné & Giesbert, 1994), Espírito Santo, Rio de Janeiro (Costa Lima, 1955), São Paulo (Costa Lima, 1936), Paraná (Silva et al, 1968), Santa Catarina , Rio Grande do Sul (Buck, 1959)].…”
Section: Fêmea: Desconhecidaunclassified